External auditory canal obstruction due to osteoma in a Syrian male patient: long-standing neglect and delayed diagnosis in a rural setting—a case report - Bilal Hasan; Zulfiqar Hamdan; Lina Mohamad; Nagham Salem (Journal of Medical Case Reports)
Abstract Introduction Osteomas are benign bone tumors most commonly found in the external auditory canal, often mistaken for exostoses. While typically asymptomatic, larger osteomas can cause hearing loss, tinnitus, or canal obstruction. Case presentation A 20-year-old Syrian male presented with progressive right-sided hearing loss and difficulty inserting ear-cleaning tools, persisting since age 13 years. Previous conservative management with canal dilation was unsuccessful. Examination revealed partial occlusion of the external auditory canal, and otoscopy was not possible owing to the stenosis. Axial and three-dimensional computed tomography scans identified a bony bridge connecting the mastoid and zygomatic processes, obstructing the canal. Audiometry confirmed conductive hearing loss (40–50 dB air–bone gap). The patient underwent postauricular excision, bony drilling, and canal reconstruction. Postoperatively, the air–bone gap resolved, and canal patency was restored. Histopathology confirmed a benign osteoma. Conclusion Despite being benign, this condition warrants more research to address knowledge gaps and improve diagnosis, especially in underserved areas. Better understanding and awareness could significantly enhance patient management and quality of life.